2014
DOI: 10.1016/j.gheart.2014.03.2454
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Ancient and Modern Egyptians:The Horus Study

Abstract: The presence and severity of atherosclerotic vascular disease correlates strongly to age in both ancient and modern Egyptians. There is a striking correlation in the distribution of the number of vascular beds involved. Atherosclerotic calcifications are seen in the aortoiliac beds almost a decade earlier than in the coronary and carotid beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Over the last few years there has been great debate about the presence and extent of arteriosclerosis in historic individuals. There is increasing evidence from various populations from all over the world and of different times that arteriosclerosis was a common feature [ 35 – 40 ]. The present case of arteriosclerosis contributes to this debate insofar as Count Heinrich suffered from significant arteriosclerosis, not very surprising given his advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years there has been great debate about the presence and extent of arteriosclerosis in historic individuals. There is increasing evidence from various populations from all over the world and of different times that arteriosclerosis was a common feature [ 35 – 40 ]. The present case of arteriosclerosis contributes to this debate insofar as Count Heinrich suffered from significant arteriosclerosis, not very surprising given his advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered atheromatous plaques in more than a third of the mummies examined, confirming that atherosclerosis was a disease spread across four ancient different populations, with similar percentages to those found of modern societies. 12 Moreover, there was a clear relationship between the severity of atherosclerotic disease and aging, with evidence of multiple atherosclerotic lesions in the older age groups. Atherosclerosis was prevalent in the aorta, followed by the peripheral vessels, carotids, iliacs and coronaries, with no frequency difference between sexes.…”
Section: Historical Surveymentioning
confidence: 99%
“…The Horus study of four ancient populations showed that atherosclerosis - evidenced by arterial calcifications found on whole-body CT scan of the mummies - was common in preindustrial civilizations including preagricultural hunter-gatherers 4143. A study compared patterns and demographic characteristics of atherosclerosis among Egyptians from ancient and modern times, showing that the extent and severity of atherosclerotic vascular disease were strongly related to aging in both modern and ancient Egyptians, regardless of gender 44. Nevertheless, the ancient elite classes were more affected by atherosclerosis than the less well-off ones, likely due to the high intake of very atherogenic foods (fatty meats, such as goose and pork; abundant consumption of sugar and honey) in their diet, as well as for a greater tendency to overweight and diabetes 45.…”
Section: Diet and Atherosclerosismentioning
confidence: 99%